Najpiękniejszy rękopis średniowiecza - Księga z Kells - Wasilewska, Jolanta (Archiwa, Biblioteki i Muzea Kościelne, 2015)
The Book of Kells (lat. Codex Cenannensis, Irish: Leabhar Cheanannais), also known as the Gospels of Kells or the Gospels of St. Columba - a manuscript believed to have been created c. 800, richly illuminated by Celtic monks from the monastery on the island of Iona. The manuscript is considered to be one of the most valuable and important monuments of Irish Christianity and works of Gaelic art, which survived to our times. Its fame rests mainly on glamor and artistry decorations that have no equal. Great compositions filling entire pages, craftsmanship decorations and ornamentation of initials used to highlight the text, make The Book of Kells a unique and unrepeatable work of art. Since the mid-seventeenth century The Book of Kells is permanently stored in the Library of Trinity College Dublin (signature MS 58). In 2011 it has been inscribed on the UNESCO Memory of the World Register.